Crbn modulates calcium influx by regulating Orai1 during efferocytosis - Hyunji Moon (Nature Portfolio, 2020)
Calcium flux must be carefully controlled during the phagocytosis of apoptotic cells (efferocytosis), although how this occurs is not fully understood. Here, the authors show that the Cereblon E3 ligase regulates Orai1 degradation and subsequently SOCE-mediated calcium influx.